Physical Activity and Diet in a Global Pandemic: An Investigation of the Impact of COVID-19 on Factors Relevant for Musculoskeletal Health at Two Different Stages of the Lifecourse - Bevilacqua, Gregorio; D’Angelo, Stefania; Linaker, Cathy; Paul, Alice; Bloom, Ilse; Zhang, Jean; Laskou, Faidra; Cooper, Cyrus; Ward, Kate A.; Walker-Bone, Karen; Dennison, Elaine M. (Frontiers in Endocrinology, 2022)
Background: Physical activity, nutrition and other lifestyle factors play important roles in maintaining musculoskeletal health. The coronavirus disease (COVID-19) originated in late 2019, spread globally to be declared a pandemic by the World Health Organisation in March 2020, and led to widespread behaviour change. The aim of this study was to use two existing cohorts, the Hertfordshire Cohort Study (HCS) and Health and Employment After Fifty Study (HEAF), to understand how wave one of the COVID-19 pandemic impacted lifestyle factors associated with musculoskeletal health in the UK. Methods: 125 eligible participants, 65 males and 60 females (drawn from the HCS study, median (IQR) age 84.3 (82.4-86.6) years, all Caucasian, and community dwelling) were contacted by telephone and asked to complete a questionnaire administered by a trained researcher. Data collection occurred over the period July 2020 to February 2021. 2469 participants, 1086 men and 1383 women (drawn from the HEAF study, median age 65.7 (62.0-69.3) years, mostly Caucasian and community dwelling) completed an online questionnaire in March 2021. Results: In HCS, 47% respondents reported being less physically active than before the pandemic (and only 5% more so), 27% said they consumed less alcohol compared to pre-pandemic times (and only 3% more so), and 18% reported eating less than before, although quality of diet was generally unchanged over this timeframe surveyed. In HEAF, 44% participants said they were less active than before the pandemic, while 17% reported being more active. The majority of participants reported no changes in alcohol consumption and diet; however, 19% said they drank more than before (32% of which was above recommended levels), 16% said their diet was less healthy, and 19% reported eating more than before. Conclusion: We have reported the experience of the first wave of the COVID-19 pandemic among participants of two Caucasian community dwelling UK cohorts, highlighting the impact of the pandemic on lifestyle factors associated with musculoskeletal health. Changed physical activity levels were reported in a high proportion of respondents in both studies; an investigation of reversibility of these changes is required.